A hexameric [MnIII18Na6] wheel based on [MnIII3O]7+ sub-units. Issue 87 (29th September 2016) - Manoli, Maria; Inglis, Ross; Piligkos, Stergios; Yanhua, Lan; Wernsdorfer, Wolfgang; Brechin, Euan K.; Tasiopoulos, Anastasios J.
Abstract : A nano-sized hexameric [MnIII3Na]6 molecular aggregate is reported which is the second largest oxime-based Mn cluster known to date, the largest member of the family of molecular oligomers based on [Mn3 ] triangles, and the only one with a wheel-like metal topology. Abstract : A novel hexameric [MnIII18Na6 ] wheel-like aggregate consisting of [MnIII3O] triangles is reported. It is the second highest nuclearity oxime-based Mn cluster, the largest member of the recently-developed family of molecular oligomers based on [MnIII3O] triangles, and the only one with a wheel-like metal topology.